Enhanced Airglow Signature Observed at Titan in Response to its Fluctuating Magnetospheric Environment. Issue 17 (14th September 2018) - Royer, E. M.; Esposito, L. W.; Crary, F.; Wahlund, J.‐E.
Abstract: On rare occasions Titan has been observed in the magnetosheath, where the solar wind interferes with the regular magnetic field generated by Saturn. This particular orbital position allows for a deeper investigation of Titan's upper atmosphere response to its highly energetic magnetospheric environment. Although solar extreme ultraviolet radiation is known to be the main source of ionization in Titan's upper atmosphere, magnetospheric particle precipitation can also account for about 10% of the ionization process. We are reporting here on ultraviolet observations of Titan airglow enhancements occurring while the spacecraft and Titan are known to have been exposed to the magnetosheath environment. Using remote sensing Cassini Ultraviolet Imaging Spectrograph observations of Titan in correlation with in situ Cassini Plasma Spectrometer measurements, we present evidence of Titan's upper atmosphere response to an electron burst crossing the magnetosheath at the time of the T32 flyby, on 13 June 2007. Plain Language Summary: Most of the time, Titan is embedded in Saturn's magnetosphere. The solar wind pressure on Saturn's magnetic field defines the size of the magnetospheric envelop around the planet. On rare occasion, this pressure is strong enough to reduce the size of Saturn's magnetospheric envelop, leaving Titan outside of it. We have been observing Titan and its immediate environment during such a configuration. The compression of the magnetic envelop allows for Titan uppermost layer of its atmosphere to directly interact with solar wind particles. We are reporting here on an observation showing a strong and sudden brightening of the upper atmosphere of Titan correlated with simultaneous measurements of an increase in electron energy around the satellite. Using remote sensing Cassini Ultraviolet Imaging Spectrograph observations of Titan in correlation with in situ Cassini Plasma Spectrometer measurements, we present evidence of Titan's upper atmosphere response to an electron burst passing by the Saturn's system at the time of the T32 flyby, on 13 June 2007, providing a better understanding of how magnetospheric environment and planetary atmospheres interact together. Key Points: We observed Titan's upper atmosphere and its magnetospheric environment, correlating data from an in situ and a remote sensing instrument An electron burst detected in Titan vicinity is most likely the source of the enhanced airglow episode observed in its upper atmosphere The presence of Titan in the magnetosheath facilitates the detection of enhanced airglow events